Familial paracentric inversion of chromosome 15 (q15q24). Issue 6 (December 1984) - Del Porto, G; D'Alessandro, E; De Matteis, C; D'Innocenzo, R; Baldi, M; Pachi, A; Cappa, F
Abstract : A paracentric inversion of chromosome 15 was observed in the father of two infants who died 29 days and 24 hours, respectively, after birth. The same inversion was found in two sisters of the proband.